Effect of microwave energy on dehydration process of sodium iodide used in single crystal growing - Voloshko, A.Yu.; Grinyov, B.V.; Goriletsky, V.I.; Smirnov, N.N.; Sofronov, D.S.; Shishkin, O.V.; Kisil, E.M. (Functional Materials, 2004)
Data on sodium iodide dehydration by thermal heating and microwave drying in vacuum are compared. The use of microwave energy has been shown to provide a higher dehydration efficiency at reduced energy consumption. The working pressure range providing the best dehydration efficiency has been determined. Сопоставляются данные по обезвоживанию йодида натрия с помощью термического нагрева и вакуумной СВЧ-сушки. Показано, что применение СВЧ-энергии позволяет увеличить эффективность обезвоживания при сокращении энергозатрат. Определен диапазон рабочих давлений, при которыгх процесс обезвоживания происходит наиболее эффективно. Порівнюються дані з зневоднюванню йодиду натрію за допомогою тєрмічного на-rpiBy та вакуумної НВЧ-сушки. Показано, що застосування НВЧ-енергії дозволяє збільшити ефективність зневоднювання при скороченні енерговитрат. Визначено діапазон робочих тисків, при яких процес зневоднювання відбувається найбільш ефективно.